Co9S8@N, P-doped porous carbon electrocatalyst using biomass-derived carbon nanodots as a precursor for overall water splitting in alkaline media. Issue 31 (31st March 2017) - Liu, Rongrong; Zhang, Haimin; Zhang, Xian; Wu, Tianxing; Zhao, Huijun; Wang, Guozhong
Abstract : Using biomass-derived carbon nanodots as a precursor, Co9 S8 @N, P-doped porous carbon was fabricated by a molten-salt calcination and post-phosphorization method, and exhibits HER and OER bifunctional catalytic activity. Abstract : In this study, we first synthesized Co9 S8 @N-doped porous carbon (Co9 S8 @NC) using shrimp-shell derived carbon nanodots as a carbon/nitrogen source in the presence of CoSO4 by a one-step molten-salt calcination method. This was followed by low-temperature phosphorization in the presence of NaH2 PO2, whereby Co9 S8 @N, P-doped porous carbon (Co9 S8 @NPC) was finally obtained using the Co9 S8 @NC as a precursor. The results demonstrated that the molten-salt calcination approach can effectively create a pyrolytic product with a porous structure and improve the material's surface area, which is favourable for electrocatalysis-related mass transport and the exposure of catalytic active sites during electrocatalysis. As an electrocatalyst, Co9 S8 @NPC exhibits higher catalytic activity for the hydrogen evolution reaction (HER) than Co9 S8 @NC in an alkaline medium. Among all the investigated Co9 S8 @NPC catalysts, Co9 S8 @NPC-10 (mass ratio of NaH2 PO2 to Co9 S8 @NC = 10 : 1) displays the best HER activity with an overpotential of 261 mV at 10 mA cm −2 in the alkaline medium. Interestingly, Co9 S8 @NPC-10 also displays good catalytic activity for the oxygen evolution reaction (OER) in this study. Owing to its bifunctional catalytic activity towards the HER and OER, the fabricated Co9 S8 @NPC-10 was simultaneously used as an anode and cathode material to generate O2 and H2 from overall water splitting in the alkaline medium, exhibiting a nearly 100% faradaic yield. This study would be helpful to the design and development of high performance non-precious metal electrocatalysts to be applied in overall water splitting to produce H2 and O2 .